Pivotal results of SELECT-MDS-1 phase 3 study of tamibarotene with azacitidine in newly diagnosed higher-risk MDS - Amy E. DeZern; Sylvain Thepot; Stephane de Botton; Andrea Patriarca; Dries Deeren; Jose-Miguel Torregrossa-Diaz; Giovanni Marconi; Teresa Bernal; Juan Bergua Burgues; Blanca Xicoy; Anna Jonášová; Amer M. Zeidan; et al. (Blood Advances)
Abstract: Higher-risk myelodysplastic syndrome (HR-MDS) with RARA gene overexpression is a subset of patients (pts) with an actionable target for tamibarotene, an oral and a selective retinoic acid receptor-α (RAR-α) agonist. Tamibarotene with azacitidine (AZA) showed complete remission (CR) rates in myeloid leukemia. SELECT-MDS-1 was a phase 3 study comparing the activity of tamibarotene + AZA to placebo + AZA in these pts with newly diagnosed HR-MDS with RARA overexpression. Eligible pts had confirmed RARA overexpression, untreated MDS with higher-risk features by revised International Prognostic Scoring System (IPSS-R), and marrow blast count >5%. Pts were randomized 2:1 to receive tamibarotene + AZA or placebo + AZA, respectively. A total of 246 participants were randomized with 164 and 82 in the tamibarotene + AZA and placebo + AZA groups, respectively. Baseline characteristics included: 69.9% male; median age 75 years (range, 38-93); primary MDS, 89.8%; MDS-excess blasts-1, 48% and MDS-excess blasts-2, 52%; and IPSS-R risk category intermediate (25.5%), high (35.7%), and very high (38.9%). The study did not meet the primary end point of CR, with a P value of .2084 for the treatment effect in the tamibarotene + AZA group. The CR rates were 23.81% and 18.75% in the tamibarotene + AZA and placebo + AZA groups, respectively. The use of tamibarotene-based therapy to target RAR-α as a novel approach in pts with HR-MDS with RARA gene overexpression is not a paradigm, which can augment response rates beyond AZA monotherapy. Further explorations of alternative approaches, including those with a biomarker, to alter the natural history of this disease are warranted. This trial was registered at www.clinicaltrials.gov as #NCT04797780.